Financial accounting - Warren, Carl S.; Duchac, Jonathan E.; Reeve, James M. , 1953- (Cengage Learning, 2016)
Focuses on the forefront of innovation and change based on the needs of teaching and learning environment. This title motivates students to learn, provides practice opportunities to better prepare for exams, and helps students achieve mastery with tools to help them make connections and see the big picture